≡ (x + p)^{2} + q

Find p and q.

Find p and q.

p =

q =

q =

2

≡ (x + p)^{2} + q

Find p and q.

Find p and q.

p =

q =

q =

2

≡ (x + p)^{2} + q

Find p and q.

Find p and q.

p =

q =

q =

2

≡ (x + p)^{2} + q

Find p and q.

Find p and q.

p =

q =

q =

2

≡ m(x + p)^{2} + q

Find m, p and q.

Find m, p and q.

m =

p =

q =

p =

q =

3

≡ m(x + p)^{2} + q

Find m, p and q.

Find m, p and q.

m =

p =

q =

p =

q =

3

≡ m(x + p)^{2} + q

Find m, p and q.

Find m, p and q.

m =

p =

q =

p =

q =

3

Solve by completing the square

= 0

Leave your answer in surd form

= 0

Leave your answer in surd form

± √

3

Solve by completing the square

= 0

Leave your answer in surd form

= 0

Leave your answer in surd form

± √

3